Strengthening of Social Competency through Learning Independence of Islamic Education of Reciprocal Teaching Models with Metacognitive Approach of Primary School Students - Ahmad Yani T.; Misdah Misdah; Wahab Wahab (STKIP Singkawang, 2020)
This study aims to obtain empirical evidence on strengthening social competence (Islamic Studies subjects; Arabic script) through the independent learning of reciprocal teaching models with a metacognitive approach. The population in this study was the fifth-grade students of SD Mujahidin Pontianak City. While the sample was taken randomly from two classes from 5A and 5C to class 5 students. One class received Reciprocal Teaching (RT) model learning with a metacognitive approach as an experimental group and one class received regular learning as a control group. The instruments used in this study consisted of three types of instruments, namely: (1) observation sheets, (2) students' independent learning scales, and (3) learning outcomes tests on Islamic Education subjects. Based on the data analysis in this study, the process of strengthening social competence through student learning independence in the subject of Islamic Religious Education uses the reciprocal teaching model with a metacognitive approach practiced at SD Mujahidin Pontianak can be seen from the main component of learning (core competence). Efforts to strengthen social competence through independence can be designed through a Reciprocal Teaching model with a metacognitive approach gradually and intact. The first process starts with the development of the lesson plan as an operational design in the practice of Islamic Education learning. Development of learning components in the lesson plan, namely materials, methods, media, sources, and evaluation that are more creative, innovative. The teaching of teaching materials as a whole, which includes cognitive, affective, and psychomotor teaching materials. Second, there are differences in strengthening social competence through independent learning between students learning Islamic education using the reciprocal teaching model with a metacognitive approach and students learning Islamic education using ordinary learning models. The independent learning of students in Islamic Religious Education in the group that received reciprocal teaching model learning with a metacognitive approach was better than the control group.